Changes in macrobenthos communities during the invasive Spartina alterniflora removal and mangrove restoration - Lin, Lin; Guo, Yuqing; Wang, Guangzhao; Feng, Shilong; Liu, Kai; Hu, Mingcheng; Ye, Mouxin; Cao, Chunxi; Chen, Ruohai; Ding, Silong; Peng, Zenghui; Ji, Fenfen; et al. (Frontiers in Marine Science, 2025)
BackgroundThe mangrove ecosystem has been severely threatened by the invasive species Spartina alterniflora for a long time. The macrobenthos diversity, as a biological indicator for assessing ecosystem sensitivity, can respond sensitively to the removal of the invasive S. alterniflora. Traditional morphological method has been commonly used to study macrobenthos diversity. However, it is difficult to comprehensively and accurately assess using traditional morphological method alone. Few studies have systematically assessed the effectiveness of environmental DNA in monitoring the diversity of macrobenthos in mangrove ecosystems.MethodsTraditional morphological method and eDNA metabarcoding (using COI primers) were combined to analyze changes in macrobenthos diversity in September (before S. alterniflora removal), October (after S. alterniflora removal but before mangrove planting), and December (after S. alterniflora removal and mangrove planting) of 2022 at the Quanzhou Bay Mangrove Wetland Nature Reserve, Fujian Province, China.ResultsThe results showed that 26 species were identified using traditional morphological method, while 212 species were identified through eDNA metabarcoding, especially more Arthropod were detected. However, no species were found to be common between the two methods at the species level. In terms of abundance, Arthropods and Annelids were the dominant groups for two methods, both 28.38% in the traditional morphological method and 38.38% and 32.94% in the eDNA metabarcoding, respectively. Additionally, the traditional morphological method indicated that following the removal of S. alterniflora, species richness, density, biomass, and diversity indices of macrobenthos initially declined, but subsequently showed a consistent recovery trend.DiscussionOur study suggests that eDNA metabarcoding has tremendous potential to monitor macrobenthos diversity, but shows low consistency in species with traditional method. For broader application in macrobenthos diversity using eDNA metabarcoding, further optimization is needed. Additionally, the results suggested that after the removal of S. alterniflora, macrobenthos diversity initially declined but gradually recovered, and long-term monitoring is warranted in order to better understand the changes in macrobenthos diversity with planting of mangroves.